Tracer study of Bachelor of Science in Mathematics - Maria Theresa B. Kalaw (International Journal of Evaluation and Research in Education (IJERE), 2019)
This research aimed to determine the employability of its graduates as well as the strengths and weaknesses of the Bachelor of Science in Mathematics (BSM) program of a Philippine Higher Educational Institution. Adapting the Commission on Higher Education (CHED) Graduate Tracer Survey Questionnaire, the study provided data that were used as basis in the review and revision of the said program. Results of this research may be used to answer the needs of society by adjusting the curriculum to meet the needs of the 21st century learners, help prepare the students not only for the world of work and land relevant employment but also to innovate in the future. Results of the study were utilized to document the employment characteristics, transition to employment and the level of satisfaction of the fifty (50) BSM graduates in terms of the level of satisfaction of the school’s services, learning environment and facilities. The findings revealed that the graduates claimed their pre-service training under the BSM program helped them acquire 21st Century skills and competencies which were not only effective and adequate but also relevant in responding to the demands of their chosen occupations. Providing soft training on applied computer software, forming partnership with software developers, offering foreign language and major courses that merge machine learning and data science were some of the recommendations suggested by the graduates to further improve the BS Mathematics program.